Vanadium positive electrode material with high-stability crystal face structure and preparation method of vanadium positive electrode material

By using a synergistic intercalation-anchondron-2-sulfonate strategy of metal zinc ions and sodium anthraquinone-2-sulfonate in vanadium pentoxide positive electrode material, the problems of instability in traditional materials and slow ion diffusion are solved, and high stability is achieved and rapid ion diffusion improve cycle stability and energy storage performance.

CN119419225AActive Publication Date: 2025-02-11ANHUI POLYTECHNIC UNIV

Patent Information

Application Number
CN202411300489.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-02-11
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

Traditional vanadium pentoxide positive electrode materials have unstable structure and slow ion diffusion in zinc ion batteries, resulting in a decrease in cycle stability and energy storage performance.

Method used

Using the synergistic intercalation-anchondone-2-sulfonate strategy of metal zinc ions and organic molecule sodium anthraquinone-2-sulfonate, zinc ions and sodium anthraquinone-2-sulfonate were embedded in vanadium pentoxide through hydrothermal method to form high stability Crystal surface structure.

Benefits of technology

It achieves high stability and rapid ion diffusion of vanadium-based materials, improves cycle stability and zinc storage rate performance, and maintains high consistency after 1,000 cycle charge and discharge tests.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419225A_ABST
    Figure CN119419225A_ABST
Patent Text Reader

Abstract

The invention discloses a vanadium positive electrode material with a high-stability crystal face structure and a preparation method thereof, and belongs to the technical field of zinc ion batteries, and the preparation method comprises the following steps: step S1, adding vanadium pentoxide powder into a beaker, then adding deionized water, stirring and mixing, then adding zinc sulfate and anthraquinone-2-sodium sulfonate, stirring and mixing, and then adding sodium hydroxide, stirring and mixing; finally adding hydrogen peroxide, stirring and mixing to obtain a modified solution; and S2, adding the modification solution into a reaction kettle, then adding the pretreated carbon cloth, immersing the pretreated carbon cloth into the modification solution, carrying out hydrothermal reaction, reducing the pressure, cooling to room temperature, washing with water for multiple times, and drying to obtain the vanadium positive electrode material with the high-stability crystal face structure, through pre-intercalation of zinc ions and synergistic anchoring of anthraquinone-2-sodium sulfonate, the ion migration rate of the positive electrode material is improved, meanwhile, a stable crystal space structure is formed, a wide-area and stable microscopic channel is provided in the ion intercalation-deintercalation process, and the zinc storage rate performance and the cycle stability are enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of zinc ion batteries, and in particular relates to a vanadium-based positive electrode material with a high-stable crystal plane structure and a preparation method thereof. Background Art

[0002] Flexible battery systems focus on flexible lithium-ion batteries, flexible sodium-ion batteries, and flexible zinc-ion batteries. Compared with flexible lithium-ion batteries and flexible sodium-ion batteries, flexible zinc-ion batteries have the characteristics of simple preparation process (no vacuum environment required), non-toxic electrolyte (aqueous electrolyte), long cycle life (charge and discharge cycles can reach 10,000 times), high capacity (theoretical capacity is about 820mAh / g) and high safety (no risk of fire and explosion), and are considered to be an alternative for the next generation of energy storage. Vanadium-based positive electrode materials such as vanadium pentoxide and ammonium vanadate have attracted widespread attention from researchers due to their high discharge specific capacity and long cycle life. Although vanadium-based positive electrode materials can carry large volumes of zinc ions, their unstable structure, weak conductivity, and low ion diffusion coefficient will cause their capacity to decay rapidly during the cycle. Therefore, how to effectively introduce guest intercalation materials while forming a stable crystal space structure and provide wide and stable microscopic channels during the ion insertion-extraction process needs to be solved urgently.

[0003] The current effective strategy for adjusting the structure of the layered restricted interlayer region is the chemical pre-intercalation synthesis method, which opens up a powerful way to construct new phases, hybrid materials and two-dimensional heterogeneous interfaces and regulate electrochemical charge storage properties. In the prior art, lithium ions are inserted into the interlayer of the hydrous vanadium pentoxide structure by hydrothermal method, and a long cycle life aqueous ZIBs positive electrode material is successfully prepared. Lithium metal ion doping and structural water retention of Li x V2O5·nH2O further expands the interlayer distance of the positive electrode material, effectively solving the bottleneck problems of slow ion diffusion and unstable material structure during the charge and discharge process of traditional vanadium pentoxide as the positive electrode material of aqueous zinc ion batteries, and improving the cycle stability. However, this method can only increase the ion migration rate. The zinc ion deintercalation process will cause the lattice "breathing effect", causing the generation of interlayer internal stress. It is impossible to effectively introduce the guest intercalation material and form a stable crystal space structure at the same time. It is difficult to provide a wide and stable microscopic channel during the ion insertion-extraction process. The Chinese invention patent with announcement number CN110364726B discloses a preparation method and application of a dual-ion doped vanadium pentoxide positive electrode material. The method uses a hydrothermal method to carry out Na + 、Zn 2+ Double ion doping, and through Na + 、Zn 2+ and V2O5 to control the molar ratio of Zn x Na yThe doping amount in the V2O5 nanowires can adjust the stability of the internal structure of the material, effectively inhibit the dissolution of vanadium compounds in the electrolyte, and effectively increase the capacity of the material. However, even after double ion doping, the crystal surface structure of the vanadium-based material is not modified and anchored stably, resulting in the collapse of the lattice size of the vanadium-based material during multiple charge and discharge processes, resulting in a decrease in cycle stability. Moreover, the traditional vanadium pentoxide positive electrode material will inevitably cause structural expansion and recovery during the ion embedding and extraction process. During rapid charge and discharge or multiple charge and discharge processes, this irreversible structural change will inevitably lead to a decrease in the ion migration rate and a decrease in the energy storage performance of the electroactive material. Summary of the invention

[0004] The present invention proposes a method for preparing a vanadium-based positive electrode material with a high-stable crystal plane structure, designs a new strategy of "cooperative intercalation-anchoring" of metal zinc ions and organic molecule sodium anthraquinone-2-sulfonate to the positive electrode material, which can simultaneously realize the pre-intercalation of embedding and deintercalating metal ions and the co-"anchoring" of the organic molecules to the positive electrode material crystal system, thereby realizing the controllable growth of the vanadium-based positive electrode material with a high-stable crystal plane structure, and solving the problems of slow ion diffusion and unstable material structure of traditional vanadium pentoxide materials as the positive electrode of aqueous zinc ion batteries during the charging and discharging process.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A method for preparing a vanadium-based positive electrode material with a high-stable crystal plane structure comprises the following steps:

[0007] Step S1: Modification solution preparation

[0008] Add vanadium pentoxide powder to a beaker, then add deionized water and stir and mix for 10-30 minutes to fully dissolve the vanadium pentoxide powder, then add zinc sulfate and sodium anthraquinone-2-sulfonate and stir and mix for 10-30 minutes, and finally add hydrogen peroxide and stir and mix to obtain a uniform, transparent red modification solution;

[0009] Step S2: Preparation of positive electrode materials

[0010] The modified solution is added into a polytetrafluoroethylene-lined reactor, and then the pretreated carbon cloth is added and immersed in the modified solution for hydrothermal reaction, the pressure is reduced, the mixture is cooled to room temperature, the active substances that are not firmly attached to the surface are washed with water for multiple times, and the mixture is dried to obtain a vanadium-based positive electrode material with a highly stable crystal plane structure.

[0011] Furthermore, the usage ratio of the pretreated carbon cloth, vanadium pentoxide powder, deionized water, zinc sulfate, sodium anthraquinone-2-sulfonate and hydrogen peroxide is 10g:4.5-5g:562.5-625mL:0.35-0.5g:0.3-0.5g:4.5-5g.

[0012] Furthermore, the carbon cloth is pretreated by the following method:

[0013] The carbon cloth is cleaned with hydrochloric acid, acetone, ethanol and deionized water in sequence to remove impurities on the surface of the carbon cloth. After cleaning, the carbon cloth is dried to obtain a pretreated carbon cloth.

[0014] Furthermore, the purity of the vanadium pentoxide powder is 90-98%.

[0015] Furthermore, the temperature of the hydrothermal reaction is 120-140° C., and the time of the hydrothermal reaction is 6-10 h.

[0016] A highly stable crystal plane structure vanadium-based positive electrode material is prepared by the above preparation method.

[0017] Beneficial effects:

[0018] The invention uses carbon fiber cloth as a carrier, and selects zinc ions and anthraquinone-2-sodium sulfonate with rich groups as a modification system to achieve the expansion of the interplanar spacing of vanadium materials and the stabilization of the crystal structure. Firstly, zinc ions can be pre-intercalated between the layers of vanadium materials to expand the interplanar spacing of vanadium materials, so that the ion diffusion rate of zinc ions is accelerated during the insertion-extraction process, and the theoretical capacity is improved. Then, anthraquinone-2-sodium sulfonate is chemically combined with the pre-intercalated vanadium materials, and the crystal structure is synergistically anchored by chemical bonds, so that the crystal structure of the vanadium materials and the zinc ions after insertion can be stabilized, so that the crystal structure will not be destroyed during the ion migration process, thereby improving the stability of the crystal surface. The synergistic optimization of the crystal surface structure system of vanadium-based materials by the addition of vanadium pentoxide and sodium anthraquinone-2-sulfonate improves the ion migration rate and solves the problem of interlayer internal stress caused by the lattice "breathing effect" during the zinc ion deintercalation process. By introducing guest intercalation substances and forming a stable crystal space structure at the same time, a wide and stable microscopic channel is provided during the ion insertion and extraction process, thereby enhancing the zinc storage rate performance and cycle stability. After 1000 cycles of charge and discharge tests, the charge transfer resistance of the positive electrode material can still be highly consistent, effectively solving the bottleneck problems of slow ion diffusion and unstable material structure of traditional vanadium pentoxide materials as the positive electrode of aqueous zinc-ion batteries during charge and discharge. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The present invention will be further described below in conjunction with the accompanying drawings.

[0020] Figure 1 is a SEM image of the positive electrode material obtained in Example 3 of the present invention;

[0021] Figure 2 This is a SEM image of the positive electrode material obtained in Comparative Example 1 of the present invention;

[0022] Figure 3This is a SEM image of the positive electrode material obtained in Comparative Example 2 of the present invention;

[0023] Figure 4 This is a SEM image of the positive electrode material obtained in Comparative Example 3 of the present invention;

[0024] Figure 5 is a TEM image of the positive electrode material obtained in Example 3 of the present invention;

[0025] Figure 6 is the XRD spectra of the positive electrode materials obtained in Example 3 and Comparative Examples 1 to 3 of the present invention;

[0026] Figure 7 0-1000 cycle in-situ EIS graphs of the positive electrode materials obtained in Example 3 and Comparative Examples 1 to 3 of the present invention;

[0027] Figure 8 The constant current charge and discharge (GCD) diagrams of the positive electrode materials obtained in Example 3 of the present invention and Comparative Examples 1 to Comparative Examples 3 are respectively 0.5 A / g, 1 A / g, 2 A / g, 4 A / g and 5 A / g, and 5 cycles;

[0028] Fig. 9 It is a 200-cycle performance diagram of the positive electrode materials prepared in Example 3 of the present invention and Comparative Examples 1 to 3 under the condition of a current density of 1 A / g;

[0029] Fig.10 It is a long cycle performance diagram of 2000 times of the positive electrode materials prepared in Example 3 of the present invention and Comparative Examples 1 to 3 under the condition of a current density of 5 A / g. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0031] Example 1

[0032] This embodiment provides a vanadium-based positive electrode material with a high-stability crystal plane structure, which is prepared by the following steps:

[0033] Step S1, washing the carbon cloth with hydrochloric acid, acetone, ethanol and deionized water in sequence, drying after washing to obtain a pretreated carbon cloth, weighing and taking 10 g of the pretreated carbon cloth for later use;

[0034] Step S2, add 4.5 g of vanadium pentoxide powder with a purity of 90% to a beaker, then add 562.5 mL of deionized water and stir and mix for 10 min, then add 0.35 g of zinc sulfate and 0.3 g of sodium anthraquinone-2-sulfonate and stir and mix for 10 min, and finally add 4.5 g of hydrogen peroxide and stir and mix to obtain a uniform transparent red modification solution;

[0035] Step S3, add all the modified solution into a polytetrafluoroethylene-lined reactor, then add 10g of pretreated carbon cloth and immerse it in the modified solution, perform hydrothermal reaction at a temperature of 120°C for 6h, reduce the pressure, cool to room temperature, wash with water several times, and dry to obtain a vanadium-based positive electrode material with a highly stable crystal plane structure.

[0036] Example 2

[0037] This embodiment provides a vanadium-based positive electrode material with a high-stability crystal plane structure, which is prepared by the following steps:

[0038] Step S1, washing the carbon cloth with hydrochloric acid, acetone, ethanol and deionized water in sequence, drying after washing to obtain a pretreated carbon cloth, weighing and taking 10 g of the pretreated carbon cloth for later use;

[0039] Step S2, add 4.8 g of vanadium pentoxide powder with a purity of 95% to a beaker, then add 600 mL of deionized water and stir and mix for 20 min, then add 0.42 g of zinc sulfate and 0.4 g of sodium anthraquinone-2-sulfonate and stir and mix for 20 min, and finally add 4.8 g of hydrogen peroxide and stir and mix to obtain a uniform transparent red modification solution;

[0040] Step S3, add all the modified solution into a polytetrafluoroethylene-lined reactor, then add 10g of pretreated carbon cloth and immerse it in the modified solution, perform hydrothermal reaction at a temperature of 130°C for 8h, reduce the pressure, cool to room temperature, wash with water several times, and dry to obtain a vanadium-based positive electrode material with a highly stable crystal plane structure.

[0041] Example 3

[0042] This embodiment provides a vanadium-based positive electrode material with a high-stability crystal plane structure, which is prepared by the following steps:

[0043] Step S1, washing the carbon cloth with hydrochloric acid, acetone, ethanol and deionized water in sequence, drying after washing to obtain a pretreated carbon cloth, weighing and taking 10 g of the pretreated carbon cloth for later use;

[0044] Step S2, add 5 g of vanadium pentoxide powder with a purity of 98% to a beaker, then add 625 mL of deionized water and stir and mix for 30 min, then add 0.5 g of zinc sulfate and 0.5 g of sodium anthraquinone-2-sulfonate and stir and mix for 30 min, and finally add 5 g of hydrogen peroxide and stir and mix to obtain a uniform transparent red modification solution;

[0045] Step S3, add all the modified solution into a polytetrafluoroethylene-lined reactor, then add 10g of pretreated carbon cloth and immerse it in the modified solution, perform hydrothermal reaction at a temperature of 140°C for 10h, reduce the pressure, cool to room temperature, wash with water several times, and dry to obtain a highly stable crystal plane structure vanadium-based positive electrode material, represented by the code Zn_AQ_VOH; its microscopic morphology under SEM is as follows Figure 1 As shown, the image under TEM is Figure 5 As shown, both zinc sulfate and sodium anthraquinone-2-sulfonate achieved intercalation complex effects on VOH, and zinc ions and sodium anthraquinone-2-sulfonate were homogeneously distributed in the system.

[0046] Comparative Example 1

[0047] The difference between this comparative example and Example 3 is that zinc sulfate and sodium anthraquinone-2-sulfonate are not added in step S2, and the other materials and steps are the same, and a common vanadium-based positive electrode material is obtained, which is represented by the code VOH. Its microscopic morphology under SEM is as follows Figure 2 shown.

[0048] Comparative Example 2

[0049] The difference between this comparative example and Example 3 is that in step S2, only zinc sulfate is added and sodium anthraquinone-2-sulfonate is not added. The remaining materials and steps are the same, and a vanadium-based positive electrode material with zinc ion intercalation is obtained, which is represented by the code Zn_VOH. Its microscopic morphology under SEM is as follows Figure 3 shown.

[0050] Comparative Example 3

[0051] The difference between this comparative example and Example 3 is that in step S2, zinc sulfate is not added, only sodium anthraquinone-2-sulfonate is added, and the other materials and steps are the same, and a vanadium-based positive electrode material modified with sodium anthraquinone-2-sulfonate is obtained, which is represented by the code AQ_VOH. Its microscopic morphology under SEM is as follows Figure 4 shown.

[0052] XRD tests were performed on the positive electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3, respectively. The XRD spectra were as follows: Figure 6 As shown, the interlayer spacing of each group of positive electrode materials was recorded, and the results are shown in Table 1;

[0053] Table 1

[0054]

[0055] From the data in Table 1, it can be seen that the introduction of zinc sulfate changes the inter-layer spacing of VOH from Increase to This indicates that zinc ions were successfully inserted into the interlayer of VOH, and after the introduction of sodium anthraquinone-2-sulfonate and zinc sulfate into the system, the interlayer spacing of VOH decreased to This indicates that sodium anthraquinone-2-sulfonate plays a bonding and anchoring role for zinc ions after they are inserted into VOH, causing the interlayer spacing to decrease slightly.

[0056] The positive electrode materials prepared in Example 3 and Comparative Examples 1 to 3 were subjected to 0-1000 cycles of in-situ EIS test. The results are as follows: Figure 7 As shown; in the process of 0-1000 cycles of charge and discharge, the charge transfer resistance (Rct, semicircle in the figure) of the electrode of comparative example 1 (VOH) is always changing, and the stability of the electron-ion interface reaction is poor; in comparative example 2, the pre-insertion of zinc ions can effectively reduce the charge transfer resistance and increase the electron transfer rate, but the electrode reaction diffusion rate is greatly reduced; comparative example 3 confirms that the introduction of sodium anthraquinone-2-sulfonate does make the charge transfer impedance of the system more stable, and the charge transfer resistance remains almost unchanged during the 0-1000 cycles of charge and discharge, and the zinc ion embedding-extraction electrode reaction process is stable; finally, the Zn_AQ_VOH composite system exhibits a highly stable electrode-electrolyte interface and electron-ion diffusion barrier (Rct is almost unchanged, only 4Ω), which proves that the modification of the positive electrode material with zinc ions and sodium anthraquinone-2-sulfonate can achieve the effect of stabilizing the crystal surface structure of the positive electrode material.

[0057] The positive electrode materials prepared in Example 3 and Comparative Examples 1 to 3 were tested with a Blue Electric CT3002A microcurrent test system. The results are shown in the figure. Figure 8-Figure 10 As shown;

[0058] Depend on Figure 8 It can be seen that under the current density of 0.5A / g, 1A / g, 2A / g, 4A / g and 5A / g, and 5 cycles of GCD test conditions, the average discharge capacity of the positive electrode material prepared in Example 3 is 392.18mAh / g, 338.2mAh / g, 285.7mAh / g, 216.3mAh / g and 183.62mAh / g, and the capacity is immediately restored to 373.54mAh / g after returning to 0.5A / g, which is much higher than the data of the positive electrode materials prepared in Comparative Examples 1 to Comparative Examples 3. Therefore, the positive electrode material prepared in Example 3 shows a higher specific capacity and better recovery performance, thereby reflecting a better electrode structure stability performance;

[0059] Depend on Fig. 9It can be seen that under the long cycle test conditions of 1 A / g and 200 cycles, the maximum discharge capacity of the positive electrode material prepared in Example 3 is 260.97 mAh / g, and the capacity retention rate after 200 cycles is 82.5%, which has excellent cycle stability; while the average capacities of Comparative Examples 1 to Comparative Examples 3 after 200 cycles are all lower than those of Example 3, especially the average capacity of Comparative Example 1 is only 90.53 mAh / g;

[0060] Depend on Fig.10 It can be seen that under the long cycle test conditions of current density of 5A / g and 2000 times, the maximum discharge capacity of the positive electrode material prepared in Example 3 is 219.4mAh / g, and the capacity retention rate after 2000 cycles is as high as 80.5%, which further illustrates that the vanadium-based positive electrode material prepared in the present invention has excellent cycle stability.

[0061] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0062] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a vanadium-based positive electrode material with a highly stable crystal plane structure, characterized in that: The steps include: Step S1, adding vanadium pentoxide powder to a beaker, then adding deionized water and stirring and mixing for 10-30 minutes, then adding zinc sulfate and sodium anthraquinone-2-sulfonate and stirring and mixing for 10-30 minutes, and finally adding hydrogen peroxide and stirring and mixing to obtain a modified solution; Step S2, adding the modification solution into the reaction kettle, then adding the pretreated carbon cloth and immersing it in the modification solution for hydrothermal reaction, reducing the pressure, cooling to room temperature, washing with water for multiple times, and drying to obtain a vanadium-based positive electrode material with a high-stable crystal plane structure.

2. The method for preparing a highly stable crystal plane structure vanadium-based positive electrode material according to claim 1, characterized in that: The dosage ratio of the pretreated carbon cloth, vanadium pentoxide powder, deionized water, zinc sulfate, sodium anthraquinone-2-sulfonate and hydrogen peroxide is 10g:4.5-5g:562.5-625mL:0.35-0.5g:0.3-0.5g:4.5-5g.

3. The method for preparing a highly stable crystal plane structure vanadium-based positive electrode material according to claim 1, characterized in that: The pretreated carbon cloth is prepared by the following method: The carbon cloth is cleaned with hydrochloric acid, acetone, ethanol and deionized water in sequence, and dried after cleaning to obtain a pretreated carbon cloth.

4. The method for preparing a highly stable crystal plane structure vanadium-based positive electrode material according to claim 2, characterized in that: The purity of the vanadium pentoxide powder is 90-98%.

5. The method for preparing a vanadium-based positive electrode material with a high-stable crystal plane structure according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 120-140° C., and the time of the hydrothermal reaction is 6-10 hours.

6. A highly stable crystal plane structure vanadium-based positive electrode material, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Preparation methods and applications of dual-ion doped vanadium pentoxide cathode materials

    CN110364726B

  • Zinc ion pre-intercalation hydrated vanadium oxide positive electrode material, preparation method and application

    CN116864661A

  • Preparation method and application of small organic molecule intercalation vanadium pentoxide material

    CN117303441A

  • Additive for aqueous zinc ion battery electrolyte and application

    CN117996232A

  • One Pedal System and Vehicle Driving Method Thereof

    KR1020220032233A

Cited By

  • Surface amorphous ammonium vanadate material as well as preparation method and application thereof

    CN120247094A